Igpaw: Loyola — Design of a Campus-Wide Augmented Reality Game Using MAGIS - Vidal, Eric Cesar E, Jr (Archīum Ateneo, 2018)
We present Igpaw: Loyola, a new location-based mobile AR (augmented reality) adventure game designed to be played within the campus grounds of the Ateneo de Manila University. Igpaw: Loyola improves upon its predecessor, Igpaw: Intramuros, by upgrading gameplay mechanics to accommodate lengthier learning modules, improving the usability of both interactive (AR) and navigation (non-AR) portions of the game, and enhancing the game authoring process with the help of an improved version of the MAGIS (Mobile Augmented-Reality Game-Engine for Instructional Support) framework. A preliminary user evaluation is also presented.